2020
DOI: 10.3390/ma13214697
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Field and Laboratory Curing Behaviour of Cold Recycled Asphalt Mixtures for Binder Courses

Abstract: The cold recycling of reclaimed asphalt (RA) for the rehabilitation of end-of-life pavements is becoming very common. Cold recycled asphalt mixtures (CRAMs) are characterised by a curing time, required to reach the material design mechanical performance. Since the laboratory simulation of the long-term field curing is not yet a standardised procedure, a CRAM was laid as binder course in a full-scale trial section that was monitored for more than two years. The comparison between field curing and oven-curing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Twenty universities and scientific centres contributed with their original research papers to this Special Issue of Materials . The issues covered can be divided into five main topics: Characterization of recycled materials in asphalt concrete mixtures, such as waste of sanitary ceramics [ 23 ], crumb rubber (CR) from waste tires [ 24 , 25 , 26 ] and reclaimed asphalt (RA) [ 27 , 28 ]; Investigation of natural [ 28 ] or bio-based [ 29 ] materials used as rejuvenators in recycled asphalt applications; Study of rheological and fatigue behaviour of bituminous materials with [ 30 ] and without [ 31 ] the use of renewable bio-materials; Evaluation of lubricant characteristics of graphite nanoplatelets [ 32 ]; Fatigue life prediction model for materials employed on long-span steel bridge decks [ 33 ]. …”
Section: Short Description Of the Articles Published In This Special ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty universities and scientific centres contributed with their original research papers to this Special Issue of Materials . The issues covered can be divided into five main topics: Characterization of recycled materials in asphalt concrete mixtures, such as waste of sanitary ceramics [ 23 ], crumb rubber (CR) from waste tires [ 24 , 25 , 26 ] and reclaimed asphalt (RA) [ 27 , 28 ]; Investigation of natural [ 28 ] or bio-based [ 29 ] materials used as rejuvenators in recycled asphalt applications; Study of rheological and fatigue behaviour of bituminous materials with [ 30 ] and without [ 31 ] the use of renewable bio-materials; Evaluation of lubricant characteristics of graphite nanoplatelets [ 32 ]; Fatigue life prediction model for materials employed on long-span steel bridge decks [ 33 ]. …”
Section: Short Description Of the Articles Published In This Special ...mentioning
confidence: 99%
“…Characterization of recycled materials in asphalt concrete mixtures, such as waste of sanitary ceramics [ 23 ], crumb rubber (CR) from waste tires [ 24 , 25 , 26 ] and reclaimed asphalt (RA) [ 27 , 28 ];…”
Section: Short Description Of the Articles Published In This Special ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Reclaimed asphalt (RA), which comes from the milling of existing asphalt pavements and is formed by aggregate clusters coated by aged bituminous binders, is widely used as an alternative component in the construction of flexible pavements [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], since it is available in large quantities (in 2019 more than 48 million of tons of RA was available in the EU [ 14 ]).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most cost-effective and environmental-friendly modes of employment of RA is represented by cold-recycling, in which RA is combined with asphalt emulsion or foamed bitumen to create a stable and durable paving mixture [ 15 ]. Although cold-recycling techniques have traditionally been used in low-volume roads due to the poorer mechanical properties of corresponding mixtures [ 8 , 16 , 17 , 18 , 19 , 20 ], promising research has been reported in which cold-recycled asphalt mixtures exhibited performance in the field comparable to that of standard bituminous layers containing exclusively virgin materials [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%